Indonesia’s Current and Future Efforts to Tackle the Issue of Deforestation - Luizinha Faria Faculto de Jesus (Universitas Budi Luhur, 2024)
Indonesia is confronted with a significant obstacle in the form of deforestation, which is caused by human activities such as agriculture and logging. This issue has far-reaching repercussions for the conservation of biodiversity and the climate change that is occurring on a worldwide scale. In order to address this problem, Indonesia has attempted a number of methods, such as moratoriums on forest removal and programs to reforest previously cleared land. As such, an analysis of Indonesia's activities to combat deforestation is presented in this study - with a particular attention on the notion that international partnerships and financial support play in bolstering these initiatives. The study, which draws on the neoliberal institutionalism theory, places an emphasis on the significance of global cooperation in efficiently addressing the difficulties posed by deforestation. In addition, this literature would also incorporate the research method of content analysis in order to better understand the arguments presented. Be that as it may, Indonesia still encounters challenges such as corruption and governance concerns that are preventing them from achieving their goals, despite the fact that they have made progress in lowering the rates of deforestation. Nonetheless, the findings of this study highlight the importance of sustaining international support and adopting inclusive strategies in order to achieve sustainable forest management at the Indonesian level. Ultimately, the study emphasizes the necessity of global partnerships and collaborative endeavors to achieve long-term success in Indonesia's efforts to combat deforestation and promote environmental sustainability, thereby emphasizing the urgency of addressing these urgent environmental concerns.